The cost of transparency: Stock market reactions to introduction of the Extractive Sector Transparency Measures Act in Canada. (October 2019) - Linder, Eric; Marbuah, George
Abstract: This paper examines stock market reactions of affected firms to the introduction of the Extractive Sector Transparency Measures Act, ESTMA. Using publicly available stock returns data on Canadian listed mining firms and oil and gas producers, an event study is employed to assess how the stock market reacted to the key events in leading up to the enactment of the Act. ESTMA mandates extractive firms listed on Canadian stock exchange to disclose payments made to governments regarding exploration of oil, natural gas, and minerals. The evidence suggests no systematic negative impact on affected firms' stock returns surrounding the analysed events. Highlights: Firm value effect of the ESTM Act examined for Canadian listed oil and gas and mining producers. Stock returns data utilized with an event study methodology to assess series of events leading to the Act's enactment. Results suggest no robust negative effect on firms' stock returns.